Periodismo medioambiental. Tratamiento informativo en los medios digitales de la Provincia de Los Ríos - Cuenca Cuenca, Roque Feller (2021)
The environment today is an issue that worries the productive and scientific sectors of the world community. In addition to journalism as a specialization and source of information, for this reason this research addresses how the digital media in the province of Los Ríos address this issue of great importance for society. In addition, with the elaboration of this work, it was possible to show the spaces that both journalists and the digital press give to environmental issues; If the professionals who carry out this activity are specialists, also the importance of the information and how it reaches the community and the impact it produces. The work is based on the human rights of the ONU in terms of freedom of communication of professionals, in the constitution of the Republic of Ecuador in terms of the right of nature, in environmental laws related to the care of the environment, in the organic law of communication. and in concepts of: environmental researchers, university professors, journalists specialized in environmental issues, who endorse the subject and the form of the research carried out.